Speech-language Pathology in Acute Pediatric Chemical or Button Battery Ingestion Injury. Issue 1 (January 2017) - Follent, Anna M.; Rumbach, Anna F.; Ward, Elizabeth C.; Dodrill, Pamela; Lewindon, Peter
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: Dysphagia is a common consequence of pediatric ingestion injury, yet there is a lack of data relating to recommencement of oral (per os; PO) intake or use of feeding therapy. We describe patterns of early PO intake, and referral to speech-language pathology (SLP) for feeding therapy, during the acute admission of a pediatric cohort postchemical or button battery ingestion injury. Methods: Retrospective chart review of pediatric ingestion injuries admitted to a quaternary hospital from 2008 to 2013. Clinical parameters, PO intake progression, and nature of referrals for feeding therapy during the acute admission were examined. Results: Fifty-one children (26 boys; mean age: 31.5, range 4–170 months) were identified (75% with grade II or III mucosal injuries), of whom 31 (60%) had impaired PO intake. Of these, 5 recommenced premorbid PO intake during admission. At discharge, 16 remained on modified PO intake, and 10 remained nil PO. Eight (26%) were referred to SLP for feeding therapy during acute admission, or within 4 months of discharge. Feeding therapy-referred children were more likely to have pediatric intensive care admission (PICU) (100% vs 26%), and longer hospital admission (36.1 vs 9.3 days for those not referred). Conclusions: More than half of the cohort had impaired PO intake, and one-third were nil PO at time of discharge. Referrals for feeding therapy were limited. Our findings may provide some guidance for clinicians, patients, and their families regarding possible PO intake recovery patterns, as well as provide background for evaluating the potential for feeding therapy and SLP involvement within this population.